Relationship between functional movement screening (FMS) scores and balance and strength performance in young male athletes - Şükran İribalcı; Mert Aydoğmuş; Serkan Revan; Harun Genç (Journal of Men's Health)
Functional movement screening (FMS) is a test developed to evaluate the fundamental movement patterns underlying both sports performance and injury risk. This study aims at evaluating the relationships between FMS test scores and strength and balance performance in young male athletes. Male athletes (n = 41, mean age 13.5 ± 1.7 years) interested in team sports participated in the study voluntarily. FMS scores, dynamic balance, static balance and strength values of the participants were determined. Shapiro-Wilk test was applied to determine if the data were normally distributed, Pearson’s correlation coefficient analysis was used measure linear correlation, and Spearman’s rank correlation coefficient (ρ) was determined to measure the strength and direction of correlation between variables. Significant differences ranged between p = 0.01 and p = 0.05. As a result of the analyses, a positive low-level relationship for the balance measures was found between the total. FMS score and the right postero-medial (p = 0.042), and right leg composite (p = 0.30), left leg composite (p = 0.026) of the Y balance subtests while no relationships were identified in other parameters (p > 0.05). For the strength masures, a positive low-level relationship was detected between the FMS score and back strength (p = 0.016), while no relationship was found between the other strength parameters (p > 0.05). For balance and strength parameters, a moderate negative relationship was found between the FMS score and the left leg flamingo test (p = 0.009). Also according to regression analysis that the predictive power of independent variables on FMS scores is quite low. In general, it is seen that the autocorrelation between the dependent variable and predictor variables is at an acceptable level (1.768 < Durbin-Watson < 2.196). As a result, FMS scores in this athlete sample were associated with dynamic balance, static balance and strength performance.